2010
DOI: 10.1542/peds.2009-0813
|View full text |Cite
|
Sign up to set email alerts
|

Age at the Introduction of Solid Foods During the First Year and Allergic Sensitization at Age 5 Years

Abstract: OBJECTIVE: The goal was to examine the relationship between age at the introduction of solid foods during the first year of life and allergic sensitization in 5-year-old children. METHODS: We analyzed data from the Finnish Type 1 Diabetes Prediction and Prevention nutrition study, a prospective, birth cohort study. We studied 994 children with HLA-conferred susceptibility to type 1 diabetes mellitus for whom information on breastfeeding, age at the introduction of solid foods, and allergen-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
124
1
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(137 citation statements)
references
References 28 publications
6
124
1
6
Order By: Relevance
“…Этот возраст считается безопас-ным для начала введения здоровым детям прикорма [11]. Именно поэтому вводимые в рацион детей воз-раста 4-6 мес жизни продукты прикорма достаточно хорошо переносятся и усваиваются, к ним развивается толерантность.…”
Section: Discussionunclassified
“…Этот возраст считается безопас-ным для начала введения здоровым детям прикорма [11]. Именно поэтому вводимые в рацион детей воз-раста 4-6 мес жизни продукты прикорма достаточно хорошо переносятся и усваиваются, к ним развивается толерантность.…”
Section: Discussionunclassified
“…However, the concept of reverse causality has to be considered in such studies because families with a history of allergic diseases or with infants with early signs of allergy may delay the introduction of solids. Therefore, separate analyses of data for the subgroup of children with parental history of asthma or allergic rhinitis were performed in the study by Nwaru et al and results did not change, demonstrating no evidence of reverse causality (9) . These findings are consistent with those of Koplin et al who showed that infants introduced to egg at 4-6 months had a lower risk of egg allergy than those introduced to egg after that time, particularly those introduced to egg at 10-12 months of age and after 12 months of age, even after adjusting for family history of allergy and infantallergy symptoms (8) .…”
Section: Effect Of Introducing Solidsmentioning
confidence: 96%
“…5 years of age and showed that late introduction of eggs and milk was associated with increased risk of eczema. However, the retrospective collection of data on the introduction of solid foods might have introduced recall bias in that study (9) . Based on the current available data, it was proposed that early complementary food introduction may hasten and/or maintain oral mucosal tolerance rather than increase the risk of food allergy (30) .…”
Section: Effect Of Introducing Solidsmentioning
confidence: 98%
See 1 more Smart Citation
“…Зарубежными учеными установлено, что введение прикорма в более ранние или поздние сроки повышает частоту развития аллергических реакций [24][25][26]. В настоящее время детям, страдающим пищевой аллергией, прикорм назна-чают в подострый период или период ремиссии в возрас-те 5-6 мес жизни.…”
Section: Introductionunclassified